The Interplay Among Epilepsy, Parkinson’s Disease and Inflammation: Revisiting the Link through Ca2+/cAMP Signalling - Bergantin, Leandro B. (Current Neurovascular Research, 2021)
Background: Robust evidence has described that Parkinson´s disease (PD) is associated with an increased risk for developing epileptic seizures. In fact, an interplay between PD and epilepsy has been of interest for many years. An emerging hypothesis is that inflammation could link both diseases. Objective: Bearing in mind the experience of our group in the field of Ca2+/cAMP signalling pathways, this article discussed, beyond inflammation, the role of these signalling pathways in this link between PD and epilepsy. Methods: Publications involving Ca2+/cAMP signalling pathways, PD, and epilepsy (alone or combined) were collected by searching PubMed and EMBASE. Results: The comprehension of the interplay between PD and epilepsy could improve the drug therapy. In addition, a Ca2+ signalling dyshomeostasis due to Coronavirus disease 2019 (COVID-19), an emerging and rapidly evolving situation, has been reported. Conclusion: Thus, this article also debated recent findings about therapeutics involving Ca2+ channel blockers for preventing Ca2+ signalling dyshomeostasis due to COVID-19, including the correlation among COVID-19, epilepsy, and PD.
Keywords: Coronavirus disease 2019 (COVID-19)